ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI SAYURAN DALAM PROGRAM TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi Kasus di Kelompok Tani Harapan Jaya Binaan PT Kaltim Prima Coal) - Lathifaturrahmah Lathifaturrahmah; Ahmad Choibar Tridakusumah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Companies as national economic development actors must be able to contribute to improve the welfare of the community and the surrounding environment, this concern is proved by the Corporate Social Responsibility (CSR) program, including PT. Kaltim Prima Coal, which has implemented Social Responsibility for Agibusiness Development for farmers around the mine since 1999. One of the groups that becomes the beneficiary is Harapan Jaya Farmer Group. The purpose of this study is (1) Describe the application of Social Responsibility/CSR of PT. KPC in Harapan Jaya farmer group, (2) Find out the income and expenditure structure of vegetable farmer households who are members of Harapan Jaya farmer group, (3) Find out the welfare level of vegetable farmer households. This study uses a qualitative design with a case study method. The selection of study sites was carried out deliberately (purposive) with the consideration that the area is the ring I area closest to the mining area. The welfare level of household was measured using the poverty line of the Sayogyo (1996), World Bank, and BPS. The welfare level of farmers households based on Sayogyo's criteria (1996), World Bank and based on BPS poverty line criteria continued is criteria shows that 78.95% of farmer households are classified as not poor, 57.89 % of households are classified as poor and 52.63% of farmer households are classified as poor.